2006
DOI: 10.1111/j.1439-037x.2006.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Trend and Stability Analysis to Interpret Results of Long‐Term Effects of Application of Fertilizers and Manure to Cotton Grown on Rainfed Vertisols

Abstract: A field experiment was conducted from 1985-1986 to 2002-2003 on Vertisols under rainfed conditions to evaluate the effect of cropping systems and application of fertilizers and manure on seed cotton yield. To determine the long-term effects, trends and stability analyses were performed. Soil samples (0-0.15 and 0.15-0.30 m) were collected at the end of year 18 and analysed for available P and AB-DTPA extractable Zn. Among cropping systems, Asiatic diploid cotton (Gossypium arboreum) yielded 233 kg ha )1 more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Nutrient deficiencies in the N and NPK treatments might have affected plant growth and delayed boll set. Soil samples analyzed at the end of year 18 indicated AB-DTPA-extractable Zn contents to be less than the critical limit in the treatments receiving mineral fertilizers alone (Blaise et al, 2006). Furthermore, available P was also low in the treatment N-alone.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Nutrient deficiencies in the N and NPK treatments might have affected plant growth and delayed boll set. Soil samples analyzed at the end of year 18 indicated AB-DTPA-extractable Zn contents to be less than the critical limit in the treatments receiving mineral fertilizers alone (Blaise et al, 2006). Furthermore, available P was also low in the treatment N-alone.…”
Section: Discussionmentioning
confidence: 95%
“…This might be due to the fact that the cultivars used in that studies were low yielding as compared to upland cotton (Mannikar, 1993). The Asiatic cotton cultivars used in the present study have a yield potential equivalent to those of upland cotton varieties (Blaise et al, 2006). Furthermore, earlier studies were conducted over a short-term (2-3 years) period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results compared to add recommendation only complete fertilizer formulations, thus cutting out 50% of the recommendation and produced better quantity and fertilizer formulations, and minimize food contamination, as well as minimize damage to the environment and human health. Blaise et al (2006) showed that to compost, decaying added to soil is a good source of potassium and soil potassium phosphorus content increased ICH transactions added to her that fertilizer analogy not addition (not clear, rewrite). A study by Biari et al (2008) when inoculated seeds of maize yellow Azotobacter bacterium and Azospirillum led to an increase in plant height and dry weight increase of total concentrations of both vegetative potassium, phosphorus, and nitrogen in plant and the hit ratios, 15.49, 166.09, 12.71 and 96.7, respectively.…”
Section: Figure 6: Impact Of Organic Waste and Isolates Bacterial In mentioning
confidence: 99%